Pain Management Strategies and Health Care Use in Community-Dwelling Individuals Living with Chronic Pain. Issue 12 (3rd March 2017) - Mann, Elizabeth G; Johnson, Ana; Gilron, Ian; VanDenKerkhof, Elizabeth G
Abstract: Objective: To describe factors associated with high clinic and emergency room (ER) use among individuals with chronic pain. Design: This study is part of a larger cross-sectional survey on the epidemiology of chronic pain in Canada. The current analysis was guided by the Andersen-Newman Service Utilization Model. Methods: Respondents (N = 702) were grouped into high (top 10%) and low (bottom 90%) users based on the number of visits made to clinics and ERs over the past year. The two groups were compared on predisposing (e.g., pain self-efficacy and sociodemographic characteristics), enabling (e.g., income and education), and need (e.g., pain characteristics and number of comorbidities) factors as well as personal health behaviors (e.g., use of medications). Binary logistic regression analysis was used to identify characteristics associated with high use in each setting. Results: High users were defined as 30 or more clinic visits or one or more ER visits. The factors associated with high clinic use in the adjusted analysis were low pain self-efficacy (odds ratio [OR] = 2.60, 95% confidence interval [CI] = 1.50–4.51), two or more comorbidities (OR = 2.13, 95% CI = 1.23–3.69), five or more pain sites (OR = 2.30, 95% CI = 1.28–4.14), and having an "other" pain diagnosis (OR = 1.78, 95% CI = 1.01–3.20). Factors that increased ER use were low pain self-efficacy (OR = 2.01, 95% CI = 1.28–3.15) and two or more comorbidities (OR = 2.31, 95% CI = 1.48–3.59), while use of alternative pain management strategies reduced ER use (OR = 0.42, 95% CI = 0.21–0.84). Conclusions: Longitudinal studies are needed to confirm if modifiable factors such as pain self-efficacy and use of alternative therapies reduce health care use.